A Phase I Study of LY3009120, a Pan-RAF Inhibitor, in Patients with Advanced or Metastatic Cancer - Sullivan, Ryan J.; Hollebecque, Antoine; Flaherty, Keith T.; Shapiro, Geoffrey I.; Rodon Ahnert, Jordi; Millward, Michael J.; Zhang, Wei; Gao, Ling; Sykes, Amanda; Willard, Melinda D.; Yu, Danni; Schade, Andrew E.; et al. (Molecular cancer therapeutics, 2020)
Mutations in ERK signaling drive a significant percentage of malignancies. LY3009120, a pan-RAF and dimer inhibitor, has preclinical activity in RAS- and BRAF-mutated cell lines including BRAF-mutant melanoma resistant to BRAF inhibitors. This multicenter, open-label, phase I clinical trial (NCT02014116) consisted of part A (dose escalation) and part B (dose confirmation) in patients with advanced/metastatic cancer. In part A, oral LY3009120 was dose escalated from 50 to 700 mg twice a day on a 28-day cycle. In part B, 300 mg LY3009120 was given twice a day. The primary objective was to identify a recommended phase II dose (RP2D). Secondary objectives were to evaluate safety, pharmacokinetics, and preliminary efficacy. Identification of pharmacodynamic biomarkers was exploratory. In parts A and B, 35 and 16 patients were treated, respectively (N = 51). In part A, 6 patients experienced eight dose-limiting toxicities. The RP2D was 300 mg twice a day. Common (>10%) any-grade drug-related treatment-emergent adverse events were fatigue (n = 15), nausea (n = 12), dermatitis acneiform (n = 10), decreased appetite (n = 7), and maculopapular rash (n = 7). The median duration of treatment was 4 weeks; 84% of patients completed one or two cycles of treatment. Exposures observed at 300 mg twice a day were above the preclinical concentration associated with tumor regression. Eight patients had a best overall response of stable disease; there were no complete or partial clinical responses. Despite adequate plasma exposure levels, predicted pharmacodynamic effects were not observed.